An Informatics Tool for Class-To-Class Planning and Academic-Load Evaluation - Villalobos-Cid, M; Vega-Araya, D (IEEE Computer Society, 2020)
Given its importance with regards to the health and performance of the students, the evaluation and control of the academic load have come to form part of a critical component of the educational process. Several universities around the world have performed studies evaluating their programs by contrasting the planned and effective academic load using a credit system. Most of them have used strategies based on interviews, surveys, questionnaires and logbooks to quantify the effective load. In addition, it has become necessary to define academic programs with activities and load planned according to a uniform criterion. To evaluate the programs of our department, we propose a strategy based on three stages: (1) the designing of an informatic tool which allows academics to plan the class-To-class activities of each course by considering load, (2) holding a set of meetings with academics and students to discuss the planned and effective load of the courses, and (3) a study of the balance of the load between the different weeks of the semesters. In this manuscript, we describe the first stage of the strategy associated with the informatics tool. © 2020 IEEE.